Discussing weight loss opportunistically and effectively in family practice: a qualitative study of clinical interactions using conversation analysis in UK family practice. (19th December 2020) - Albury, Charlotte V A; Ziebland, Sue; Webb, Helena; Stokoe, Elizabeth; Aveyard, Paul
Abstract: Background: GPs are encouraged to make brief interventions to support weight loss, but they report concern about these conversations, stating that they need more details on what to say. Knowing how engage in these conversations could encourage GPs to deliver brief interventions for weight loss more frequently. Objective: To examine which specific words and phrases were successful in achieving conversational alignment and minimizing misunderstanding, contributing to effective interventions. Methods: A conversation analysis of English family practice patients participating in a trial of opportunistic weight-management interventions, which incorporated the offer of referral to community weight-management services (CWMS). Qualitative conversation analysis was applied to 246 consultation recordings to identify communication patterns, which contributed to clear, efficient interventions. Results: Analysis showed variation in how GPs delivered interventions. Some ways of talking created misunderstandings or misalignment, while others avoided these. There were five components of clear and efficient opportunistic weight-management referrals. These were (i) exemplifying CWMS with a recognizable brand name (ii) saying weight-management ' programme ' or ' service ', rather than ' group ' or ' club ' (iii) stating that the referral is 'free' early on (iv) saying the number CWMS visits available on referral (v) stating that the CWMS programme available was 'local'. Conclusions: When making a brief opportunistic intervention to support weight loss, clinicians can follow these five steps to create a smooth and efficient intervention. Knowing this may allay clinicians' fears about these consultations being awkward and improve adherence to guidelines. Abstract : Doctors are asked to talk to people with obesity, and to ask if they would like a referral to go to a community weight-management service (CWMS), where they can receive support to lose weight. Evidence shows they do not do this very often, and doctors say they find this difficult because they are not sure what to say. In our study we listened to 246 recordings where doctors asked if a person with obesity would like to go a CWMS. We used a method called 'conversation analysis' to study communication and find out how doctors could talk about going to weight-management services in ways which were clear, and avoided misunderstandings (which can take a long time to overcome). We found that people often did not understand what the referral was for, unless a recognizable brand name was given as an example. We also found that saying weight-management 'programme' or 'service' (instead of 'group' or 'club') avoided misunderstandings, and that saying that CWMS were 'free' and 'local' was important to help people with obesity make their decision. Because we have found out what doctors can say during these conversations, this could help them to offer referrals more often.